David Hume, Causation, and the Problem of Induction - Lorkowski, Chris M. (Journal of NeuroPhilosophy, 2023)
Scottish philosopher David Hume provided some of the most novel and important insights into the nature of causation. This article introduces his most important lines of thought regarding cause and effect, specifically, his analysis of causation culminating in his two definitions of causation and the Problem of Induction.